Implant-supported rehabilitation after treatment of atrophic mandibular fractures: report of two cases - Oliveira, Leandro Benetti de[UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Pereira-filho, Valfrido Antonio Pereira [UNESP] (Springer Nature, 2015)
Objective The objective of this article is to present options of rehabilitation with dental implants in two cases of severely atrophic mandibles (<10 mm) after rigid internal fixation of fractures. Patients and method Two patients who sustained fractures in severely atrophic mandibles with less than 10 mm of bone height were treated by open reduction and internal fixation through a transcervical access. Internal fixation was obtained with 2.4-mm locking reconstruction plates. The first patient presented satisfactory bone height at the area between the mental foramens and after 2 years, received flapless guided implants in the anterior mandible and an immediate protocol prosthesis. The second patient received a tent pole iliac crest autogenous graft after 2 years of fracture treatment and immediate implants. After 5 months, a protocol prosthesis was installed in the second patient. Results In both cases, the internal fixation followed AO principles for load-bearing osteosynthesis. Both prosthetic devices were Branemark protocol prosthesis. The mandibular reconstruction plates were not removed. Both patients are rehabilitated without complications and satisfied with esthetic and functional results. Conclusion With the current techniques of internal fixation, grafting, and guided implants, the treatment of atrophic mandible fractures can achieve very good results, which were previously not possible.
Keywords: Atrophic mandible; Mandibular reconstruction; Open reduction; Mandible fractures; Branemark protocol prosthesis